Material fees in the BRAC operated community schools: should it be reviewed? - Khan, Md. Kaisar Ali (BRAC Research and Evaluation Division (RED), 2019)
This study aimed at examining whether the rate of material fees that is charged to the students in the BRAC-run community schools should be reviewed. Information was collected from guardians of 550 students of 11 BRAC-run community schools. Some qualitative information was also gathered from the guardians, teachers of the concerned community schools, the members of School Management Committees, community people and concerned BRAC staff. Data show that a large proportion of the students came from extremely poor and socioeconomically backward households. Majority schools were located in the socioeconomically backward and coastal areas. Majority of the household heads were engaged in such occupations that yield very low income and had no education. Majority of them had no arable land. Thus, they were not in position to pay the material fees regularly. The findings suggest to reduce the amount of fees to an extent the service receivers will be able to pay. At the same time the existing system of fees realisation may be reviewed since it was not effective enough.